2016
DOI: 10.3402/snp.v6.31238
|View full text |Cite
|
Sign up to set email alerts
|

Regularity effect in prospective memory during aging

Abstract: BackgroundRegularity effect can affect performance in prospective memory (PM), but little is known on the cognitive processes linked to this effect. Moreover, its impacts with regard to aging remain unknown. To our knowledge, this study is the first to examine regularity effect in PM in a lifespan perspective, with a sample of young, intermediate, and older adults.Objective and designOur study examined the regularity effect in PM in three groups of participants: 28 young adults (18–30), 16 intermediate adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 71 publications
3
12
0
1
Order By: Relevance
“…In previous studies related to practice effect of TBPM, the number of participants at each level ranged from 15 to 36 (Hu and Feng, 2013; Rose et al, 2015; Blondelle et al, 2016; Waldum et al, 2016). But a larger number of participants could reduce the influence of random errors and made the experimental results more reliable (Drazen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies related to practice effect of TBPM, the number of participants at each level ranged from 15 to 36 (Hu and Feng, 2013; Rose et al, 2015; Blondelle et al, 2016; Waldum et al, 2016). But a larger number of participants could reduce the influence of random errors and made the experimental results more reliable (Drazen et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Repeated training for specific prospective memory task can also effectively improve the prospective memory performance (Yip and Man, 2013; Blondelle et al, 2016). This phenomenon is defined as the practice effect on prospective memory in the present study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first address whether the practice effect of TBPM exists. At present, some studies found that repeated TBPM tasks performed significantly better than occasional ones (Hu and Feng, 2013; Rose et al, 2015; Blondelle et al, 2016; Waldum et al, 2016). However, there is currently no research exploring its cognitive mechanism.…”
Section: Introductionmentioning
confidence: 87%
“…The first paper, by Blondelle et al [5], is very informative on the role of regularity on PM throughout life. Moreover, this paper emphasizes the need to conduct an integrative and complete cognitive assessment, and not just to assess PM by itself.…”
mentioning
confidence: 99%